Reduction in the surface energy of liquid interfaces at short length scales - Mecke, Klaus; et al. (Nature, 2000)
Liquid-vapour interfaces, particularly those involving water, are common in both natural and artificial environments. They were first described as regions of continuous variation of density(1), caused by density fluctuations within the bulk phases(2-4). In contrast, the more recent capillary-wave model(5,6) assumes a step-like local density profile across the liquid-vapour interface, whose width is the result of the propagation of thermally excited capillary waves. The model has been validated for length scales of tenths of micrometres and larger(7,8), but the structure of liquid surfaces on submicrometre length scales-where the capillary theory is expected to break down-remains poorly understood. Here we report grazing-incidence X-ray scattering experiments that allow for a complete determination of the free surface structure and surface energy for water and a range of organic liquids. We observe a large decrease of up to 75% in the surface energy of submicrometre waves that cannot be explained by capillary theory, but is in accord with the effects arising from the non-locality of attractive intermolecule interactions as predicted by a recent density functional theory(9), Our data, and the results of comparable measurements on liquid solutions, metallic alloys, surfactants, lipids and wetting films should thus provide a stringent test for any new theories that attempt to describe the structure of liquid interfaces with nanometre-scale resolution.